Ácaros (Acari) de seringueira (Hevea brasiliensis Muell. Arg., Euphorbiaceae) e de euforbiáceas espontâneas no interior dos cultivos - Bellini, Marcos R.; Feres, Reinaldo J. F.; Buosi, Renato [UNESP] (Sociedade Entomológica do Brasil, 2008)
Foram realizadas coletas trimestrais em 2001 em três cultivos de seringueira no Noroeste do estado de São Paulo. Foram amostradas três seringueiras de cada local. Nas entrelinhas das seringueiras foram coletadas quatro espécies de euforbiáceas espontâneas: Chamaesyce hirta, C. hyssopifolia, Euphorbia heterophylla e Phyllanthus tenellus. Foram coletados 8.954 ácaros de 38 espécies, pertencentes a 31 gêneros de 11 famílias. Tydeidae e Phytoseiidae tiveram maior diversidade de espécies, 9 e 7, respectivamente. As famílias mais abundantes foram Eriophyidae (3.594), Tydeidae (2.825) e Tenuipalpidae (1.027). As espécies mais abundantes nas seringueiras foram: fitófagas - Calacarus heveae Feres, Tenuipalpus heveae Baker, Lorryia sp.2, Lorryia formosa Cooreman e Lorryia sp.1; predadoras - Zetzellia quasagistemas Hernandes & Feres, Pronematus sp., Iphiseiodes zuluagai Denmark & Muma e Euseius citrifolius Denmark & Muma. Entre as euforbiáceas espontâneas, encontrou-se maior abundância de ácaros predadores em C. hirta e E. heterophylla, destacando-se Pronematus sp. e E. citrifolius, sugerindo que estas plantas possam ser importantes na manutenção daqueles predadores nos plantios de seringueira. No entanto, plantas que podem abrigar predadores, mas que também exercem forte competição (nutrientes, água etc.) com a seringueira, não podem ser sugeridas para um programa de manejo de pragas. Estudos sobre competição entre a seringueira e plantas espontâneas precisam ser conduzidos para viabilizar programas eficientes de manejo ambiental, visando o controle dos ácaros-praga da seringueira.

Quarterly samples were done in 2001 on three rubber tree plantation in the northwest of the state of São Paulo. Three rubber trees of each locality were sampled. Between the rows of rubber tree four species of spontaneous euphorbiaceous were collected: Chamaesyce hirta, C. hyssopifolia, Euphorbia heterophylla and Phyllanthus tenellus. A total of 8.954 mites of 38 species, belonging to 31 genera of 11 families were collected. Tydeidae and Phytoseiidae had the highest diversity of species, 9 and 7, respectively. The most abundant families were Eriophyidae (3.594), Tydeidae (2.825) and Tenuipalpidae (1.027). The most abundant species on the rubber trees were: phytophagous - Calacarus heveae Feres, Tenuipalpus heveae Baker, Lorryia sp.2, Lorryia formosa Cooreman and Lorryia sp.1; predators - Zetzellia quasagistemas Hernandes & Feres, Pronematus sp., Iphiseiodes zuluagai Denmark & Muma and Euseius citrifolius Denmark & Muma. Among the spontaneous euphorbiaceous, predatory mites were abundantly found on C. hirta and E. heterophylla, mainly Pronematus sp. and E. citrifolius, suggesting that these plants could be important in the maintenance of these predators in the rubber tree cultivation areas. However, plants that can shelter predators and at the same time exert strong competition (nutrients, water etc) to rubber trees, can not be recommended for pest management programs. Studies about competition between rubber trees and spontaneous plants need to be conducted for feasible efficient programs of environmental management, aiming at the control of pest mites of rubber tree.
Mites (Acari) from rubber trees (Hevea brasiliensis Muell. Arg., Euphorbiaceae) and spontaneous euphorbiaceous in rubber trees cultivation
Keywords: Manejo de pragas; Eriophyidae; Tydeidae; Tenuipalpidae; Pest management; Eriophyidae; Tydeidae; Tenuipalpidae